Changes of the pro-hormone levels of vitamin D 25(OH)D in patients with newly diagnosed pulmonary tuberculosis treatment failure - R. M. Yasinskyi; O. M. Raznatovska (Patologìâ)
In Ukraine the number of patients with newly diagnosed tuberculosis (NDTB) who successfully complete the course of treatment reaches 60–65 % today. This is while the World Health Organization (WHO) criteria for successful treatment of this category of patients is 85 %. Scientists around the world are studying the possible pathogenetic factors of treatment failure of antimycobacterial therapy in patients with tuberculosis. Nowadays, the impact of vitamin D has been widely studied in this area. Studying of the dynamics of this indicator in patients with NDTB with widespread destructive tuberculosis in the lungs and bacterial excretion with the purpose of finding new markers of progression of a specific process and failure of treatment, as well as finding possible ways of additional pathogenetic therapy to accompany patients is actual. This approach will prevent treatment failure and, as a consequence, improve treatment efficiency.